2022
DOI: 10.1136/bmjos-2021-100231
|View full text |Cite|
|
Sign up to set email alerts
|

Preclinical safety study of nacre powder in an intraosseous sheep model

Abstract: ObjectivesThe purpose of this preclinical study was to evaluate the safety, the local tissue effects and bone healing performance (osteoconduction, osseointegration) of nacre powder in a sheep intraosseous implantation model. This represents the first preclinical study to assess nacre safety and efficacy in supporting new bone formation in accordance with the ISO 10993 standard for biomedical devices.MethodsThe local tissue effects and the material performance were evaluated 8 weeks after implantation by quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…Later, Green et al demonstrated the osteogenic potential of shell nacre chips and the soluble matrix protein using human BM-MSCs [85]. Many in vivo studies have demonstrated the osteogenic potential and biocompatibility of shell nacre as a direct bone substitute [86][87][88][89][90][91][92][93][94]. Shell nacre containing hydrogel [95] and shell nacre containing calcium phosphate cement [58] showed enhanced osteogenic potential due to the addition of shell nacre.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Green et al demonstrated the osteogenic potential of shell nacre chips and the soluble matrix protein using human BM-MSCs [85]. Many in vivo studies have demonstrated the osteogenic potential and biocompatibility of shell nacre as a direct bone substitute [86][87][88][89][90][91][92][93][94]. Shell nacre containing hydrogel [95] and shell nacre containing calcium phosphate cement [58] showed enhanced osteogenic potential due to the addition of shell nacre.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained shell nacre powder was heterogenous with particle size smaller than 0.5 µm (ImageJ analysis). In contrast, other studies have reported and used shell nacre powder of larger sizes, such as 50-100 µm [50] and 42.5 µm [51], for implantation studies.…”
Section: Processing Of Shellsmentioning
confidence: 99%
“…Moreover, osteogenesis, radiopacity, osseo-integration, high fracture toughness and strength, biodegradability, anti-osteoporotic activity, and angiogenesis properties have proven shell nacre as a suitable biomaterial for hard tissue applications [45][46][47][48][49]. Although shell nacre powder has been made as a putty by mixing with autologous blood [50,51], there is no processing method to set and mould shell nacre powder into defined anatomical forms with suitable mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Since 3D printing techniques have been tremendously improved in recent years and also allow for the processing of ceramic materials, several new structurally optimized 3D printed scaffolds have been tested in large animal models [213,[229][230][231]. Some of the recent approaches also explore the potential feasibility of novel biomaterials, such as nacre [232,233], keratin [234] or the integration of plant-derived soybean peroxidase [235].…”
Section: Large Animal Modelsmentioning
confidence: 99%